2001
DOI: 10.2114/jpa.20.285
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Genistein Dosage and Resistance Exercise on Bone Loss in Ovariectomized Rats.

Abstract: This study was designed to determine whether combined treatments with genistein dosage and moderate resistance exercise would exhibit synergistically preventive effects on bone loss following the onset of menopause. Forty-one 12 wk-old female SD rats were assigned to five groups: 1) Sham operated (Sham); 2) ovariectomized (OVX-Cont); 3) OVX received genistein (OVX-GEN); 4) OVX exercised (OVX-EXE); and 5) OVX treated with both genistein and exercise (OVX-GEN-EXE). All rats were fed a low Ca (0.1%) diet ad libit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 25 publications
2
28
0
4
Order By: Relevance
“…In the present study on female rats with normal estrogen levels, both low and high doses of genistein treatment were observed to induce significant increase in BMD, BMC and bone volume, as well as inducing thicker and larger trabecular bone in the mandibular subchondral bone. These results were consistent with the above-mentioned studies on appendicular bone or vertebrae [17,18,20,[30][31][32][33][34][35][36] , indicating that the effect of genistein on mandibular subchondral bone is similar to that on appendicular bone or vertebrae. Similar to the biphasic effects of estrogen depending on dosage [37] , genistein was also observed to have a biphasic cell proliferative response, stimulation at low concentrations and inhibition at high concentrations [38][39][40] .…”
Section: Effect Of Er Silencing On the Effect Of Genistein Treatmentsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study on female rats with normal estrogen levels, both low and high doses of genistein treatment were observed to induce significant increase in BMD, BMC and bone volume, as well as inducing thicker and larger trabecular bone in the mandibular subchondral bone. These results were consistent with the above-mentioned studies on appendicular bone or vertebrae [17,18,20,[30][31][32][33][34][35][36] , indicating that the effect of genistein on mandibular subchondral bone is similar to that on appendicular bone or vertebrae. Similar to the biphasic effects of estrogen depending on dosage [37] , genistein was also observed to have a biphasic cell proliferative response, stimulation at low concentrations and inhibition at high concentrations [38][39][40] .…”
Section: Effect Of Er Silencing On the Effect Of Genistein Treatmentsupporting
confidence: 91%
“…ERα and ERβ siRNA were able to knockdown 72% and 80% of ER expression, respectively. As shown in Figure 6 and [18,20,[30][31][32][33][34][35][36] . Similarly, oral administration of genistein (54 mg·kg -1 ·d -1 ) increased BMD of the spine and hip in osteopenic postmenopausal Caucasian women with an observation period of 24 months [17] .…”
Section: Effect Of Er Silencing On the Effect Of Genistein Treatmentmentioning
confidence: 99%
“…(34) Research on ovariectomized animals have shown that combining isoflavones with exercise training can be beneficial in increasing BMD to a greater extent than either intervention used exclusively. (20,22,35) In addition, several clinical trials have shown that a combination of exercise and HRT results in an increase in BMD that is more than either intervention used exclusively. (36) This study is the first to suggest that the combined intervention of isoflavone and walking exercise for 1 year may partly prevented bone loss in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoestrogens such as genistein, resveratrol, and quercetin are widely distributed in human and animal diet and have chemopreventive properties against estrogen-responsive diseases, including inhibition of tumor cell growth (Setchell & Cassidy 1999, Miodini et al 1999, Mitchell et al 1999, Xing et al 2001, lowering serum cholesterol, and prevention of bone loss in rodents (Mizutani et al 2000, Nakajima et al 2001, Wattel et al 2003. Genistein is the most potent estrogenic compound in soy and soy products.…”
Section: Introductionmentioning
confidence: 99%